Scaling Soil Organic Carbon Sequestration for Climate Change Mitigation - Costa, Ciniro; Seabauer, Matthias; Schwarz, Benjamin; Dittmer, Kyle; Wollenberg, Eva Karoline (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Moving towards net zero GHG emissions by 2050 is likely a pre-condition for avoiding global warming higher than 1.5˚C by the end of the century. The land-use and agriculture sector can provide close to one third of this global commitment while ensuring food security, farmer resilience, and sustainable development. Protecting soil organic carbon (SOC) and sequestering carbon in organic matter-depleted soils might cost-effectively provide close to 15% of this target and support another 15% from large-scale restoration and implementation of best agronomic practices.